2002
DOI: 10.1021/jf0109367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Glycosidase Activity ofOenococcus oenion the Glycosylated Flavor Precursors of Tannat Wine during Malolactic Fermentation

Abstract: Under traditional wine-making conditions, this work examines the beta-glycosidic activity of Oenococcus oeni on glycosylated aroma compounds of Tannat wines during malolactic fermentation (MLF) by comparing the changes on selected aglycones liberated. MLF diminished the content of all the glycosylated compounds. The level of the free aroma components was slightly modified by the action of the malolactic fermentation so that the cleavage of the glycosidic linkage by the beta-glycosidic activity of O. oeni did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 34 publications
8
78
0
1
Order By: Relevance
“…However, the work was done using model wine. Indeed, while other studies corroborate these findings, much of the data indicates that although malolactic bacteria show glycosidase activity, they do not significantly contribute to glycoside hydrolysis during wine fermentations, and therefore they are unlikely to contribute significantly to wine aroma via released aroma compounds (Boido et al 2002).…”
Section: Glycoside Studies In Winementioning
confidence: 87%
See 1 more Smart Citation
“…However, the work was done using model wine. Indeed, while other studies corroborate these findings, much of the data indicates that although malolactic bacteria show glycosidase activity, they do not significantly contribute to glycoside hydrolysis during wine fermentations, and therefore they are unlikely to contribute significantly to wine aroma via released aroma compounds (Boido et al 2002).…”
Section: Glycoside Studies In Winementioning
confidence: 87%
“…In addition to effect of yeast strain on glycoside hydrolysis, many studies have been done to assess the possible ability of malolactic bacteria, in particular Oenococcus oeni, to hydrolyze volatile aroma glycosides (Barbagallo et al 2004, Boido et al 2002, D'Incecco et al 2004, Grimaldi et al 2005. Researchers compared a control fermentation without inoculation to fermentations with O. oeni and found varying decreases in glycoside concentration and varying increases in released compounds depending on the strain of O. oeni added (Ugliano et al 2003).…”
Section: Glycoside Studies In Winementioning
confidence: 99%
“…Recently, an increased interest in the sources of βG has been focused on lactic acid bacteria, especially Oenococcus oeni, the main bacterial species that conducts malolactic fermentation (MLF) in winemaking, as βG activity from grape and yeasts is limited in winemaking (Maicas & Mateo, 2005;Palmeri & Spagna, 2007;Saguir et al, 2009;Michlmayr et al, 2010b). Numerous investigations have been conducted of O. oeni strains, providing evidence of the potential βG activity for flavour enhancement in wines Boido et al, 2002;Mansfield et al, 2002;Ugliano et al, 2003;Barbagallo et al, 2004b;D'Incecco et al, 2004;Grimaldi et al, 2005a;Bloem et al, 2008;Michlmayr et al, 2010a;Gagné et al, 2011). It has been reported that possession of glycosidic activities was widespread and strain-dependent in these strains commonly used for MLF in winemaking (Grimaldi et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the possession of glycosidic activities is widespread and strain dependent among O. oeni strains (Grimaldi et al 2005a;Saguir et al 2009;Michlmayr et al 2012a). Moreover, some authors pointed out that during MLF, the final concentration of glycoside-derived volatile metabolites depended not only on the actual hydrolytic ability of individual strains, but also on the chemical structure of substrate (Boido et al 2002;Ugliano et al 2006). Thus assaying the βG activity with natural aroma precursors was necessary for an adequate evaluation of the glycosidase potential of O. oeni strains (Gagne et al 2011).…”
mentioning
confidence: 99%